Privatization in sub-Saharan Africa: On factors affecting implementation - Steve Kayizzi-Mugerwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Although privatization has been a key feature of economic policy in Africa since the early 1990s its sequencing and intensity have varied from country to country, with donor leverage being an important determinant of the pace of implementation. However, although many privatization schemes were undertaken in response to donor demands for reduced government participation in business, the process soon achieved its own dynamics. The positive view of privatization suggests that it went ahead, in spite of domestic opposition, because politicians and bureaucrats perceived real benefits to themselves and their supporters. They could influence the sales to their own benefit, while, on the other hand, a more focused public sector improved service delivery. – privatization ; positive models ; normative models ; economic policy ; sub-Saharan experience
Keywords: P16; O55; 330; Privatisierung; Zentralafrika